Profile of Ovarian Cancer Patients In Mangusada Badung Regional Public Hospital - I Gusti Ngurah Agung Trisnu Kamajaya; Bagus Ngurah Brahmantara; AA Ngurah Agung Putra Wirawan (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: Ovarian cancer is still one of the neoplasms within the gynecology scope. Besides, World Health Organization (WHO) states that ovarian cancer ranks fourth cancer in women with the lowest five-year survival rate (43%). Thus, this research aims to recognize the risk factors in patients with ovarian cancer and the commonly found characteristic.Methods: This cross-sectional observational research on 29 women diagnosed with ovarian cancer observed the age, parity, body mass index (BMI), contraception, character, and stadium. The medical record samples based on patients’ registers were obtained from the Obstetrics and Gynecologic Polyclinic in Mangusada Badung Regional Public Hospital in the January–December 2019 period, and the result data were distributed using contingency tables. Results: The data dominantly diagnosed ovarian cancer, with age distribution 51-60 years (34.5%), 44.8% with obesity, 44.8% nullipara, without a history of contraceptive use, menarche within 12 years old (41.4%), diagnosed stage IIIC (42.3%), and with serous epithelial tumor subclassification (65.5%).Conclusions: Predominant ovarian cancer is found at a late stage. The most common risk factors of developing ovarian cancer, including the age of 51–60, obesity, menarche within 12 years old, and no history of hormonal contraceptive use, are consistent with this research hypothesis about risk factors dominantly found in patients with ovarian cancer